The study of causes and effects of change order to engineering consultant practitioners - Ahmad Radzi, Ahmad Safuan (2005)
Change order or variation order as commonly known in Malaysian construction industry is a common phenomenon in any project. The nature of traditional construction process which separated the design and construction increase the chances for change order to occur in a project. There are many causes that may lead to change order in the construction project. However no matter what is the reason for their occurrences often they resulted in dispute and dissatisfaction among the parties involved in the project with regard to their resolution. Apart from that change order also resulted in project delay and difficult to manage as they often involved in new sum of additional or deduction of contract price. In general it is commonly understood that changes is an issue that involved the contactors and the client directly. However the implication of the change order to the consultants firm is also important to be reckoned. This study has been conducted with a specific focus to determine the main causes and effects of change order in Malaysian construction environment focusing on the engineering consultant's perspective. Questionnaire survey has been conducted as the main strategy in this study methodology. Samples for the study generated from the consultants firms population within Klang Valley area. The study has determined that the major causes of the change order that involved the consultant firms are resulted from the changes originated by the authorities that regulate the design process. Other major reasons are related to political influence, client request and needs to fulfill differing site conditions. The findings from the study also revealed that the consultants are unhappy with the current practice of making claims for the change order that involved them and this need to be improved. This study further provides recommendations on methods to improve the claim procedure practiced by engineering consultants on extra works caused by change order.